The “Doctrine of Love” in ʿAbd Allāh al-Anṣārī’s Manāzil al-sāʾirīn with Critical Paraphrase of ʿAbd al-Razzāq Kāshānī’s Commentary - Ali, Mukhtar H. (Journal of Sufi studies, 2016)
This article represents a preliminary inquiry into a little known and understudied commentarial tradition upon ʿAbd Allāh al-Anṣārī’s classic work on the stations of Sufism, the Manāzil al-sāʾirīn (Stations of the Wayfarers). After briefly taking stock of the considerably late commentarial tradition which this important text engendered, we will take as our case study one of the Manāzil ’s key topics, namely its sixty-first chapter on the station of love. This pivotal section on love gives profound insight into early Sufism and into the minds of two of its greatest exponents. Anṣārī discusses the station of love in detail, as he does with every chapter, in three aspects, each pertaining to the three types of wayfarers: the initiates, the elect, and the foremost of the elect. Then, we shall turn our attention to perhaps the most important Sufi commentary upon this work by an important follower of the school of Ibn al-ʿArabī, ʿAbd al-Razzāq Kāshānī, offering a guided reading of his commentary upon Anṣarī’s chapter on love in the Manāzil. A complete English translation of this chapter will be offered and appropriately contextualized.